The dynamic business model: a dynamic perspective for business models design - Cosenz, Federico; Noto, Guido (Piccola Impresa / Small Business, 2017)
Building on the extant literature on business modelling and focussing on start-up firms, this article aims at exploring the combination between conventional business model schemes and System Dynamics methodology with the intent to overcome those limitations related to a static design approach. By mapping the multiple key elements underlying value creation processes – linked according to a cause-and-effect perspective – and with the support of a simulation-based methodology, entrepreneurs may experiment and understand how the firm reacts to strategic and organizational changes in terms of performance, innovation and value creation.